Determinants Of Entrepreneurial Intention in Student's Universities in West Jakarta - Nur Hidayah; Rodhiah Rodhiah (Sultan Publisher, 2024)
: A person's achievements and experience in entrepreneurship can affect their decision to become an entrepreneur. Confidence is required, because every decision in entrepreneurship is accompanied by various risks. An important point in entrepreneurship is creating innovations to open new opportunities that have not existed previously. This study aimed to determine how achievement, confidence, and innovation affect entrepreneurial attitude. This research can enrich the knowledge sources that discuss individual attitudes and intentions toward entrepreneurship in developing countries. This study examined how achievement motivation, self-esteem, locus of control, and innovation influence entrepreneurial intention among university students in West Jakarta, Indonesia. Data were collected using Google Forms questionnaires from 80 university students in West Jakarta. The analysis was conducted using the Smart PLS-SEM. The findings reveal that achievement motivation and innovation have a positive and significant influence on entrepreneurial intention. Self-esteem showed a positive but insignificant influence, while locus of control demonstrated a negative and insignificant influence on entrepreneurial intention. The model explained (R-Square = 0.570 (57%)) 57% of the variance in entrepreneurial intention (R-square = 0.570, 57 %). These findings contribute to the understanding of the factors that shape entrepreneurial intention among university students in developing countries, particularly in the Indonesian context.